Multilevel Identity in Transnistria as a Model of State- building for a Modern Moldova - D. V. Basova (Сравнительная политика, 2015)
The article focuses on the evolution of sub-national identity of Transnistria, the prerequisites for its formations and the features of its institutional and symbolic representation.